(untitled) (The Batuk, 2020)
This paper explores the status of customer perspective of the BSC approach in Nepalese commercial banks and examines the comparative status of customer perspectives in three bank groups (state owned banks, private banks, and joint venture banks). The research design for the study is descriptive. The questionnaire survey has been used as a tool to gather knowledge about the BSC approach’s consumer perspective (an indicator of the BSC approach). The research units are considered to be three bank classes (namely, state-owned banks, private banks, and joint venture banks). The result shows that the customer perspective as for the response per respondents is satisfactory. Especially, customer perspective in terms of better brand image, careful service, and staff’s best appearance and friendliness are found good in Nepalese commercial banks.